Involving private healthcare practitioners in an urban NCD sentinel surveillance system: lessons learned from Pune, India - Kroll, Mareike; Phalkey, Revati; Dutta, Sayani; Shukla, Sharvari; Butsch, Carsten; Bharucha, Erach; Kraas, Frauke (Co-Action Publishing, 2016)
Background: Despite the rising impact of non-communicable diseases (NCDs) on public health in India, lack of quality data and routine surveillance hampers the planning process for NCD prevention and control. Current surveillance programs focus largely on communicable diseases and do not adequately include the private healthcare sector as a major source of care in cities. Objective: The objective of the study was to conceptualize, implement, and evaluate a prototype for an urban NCD sentinel surveillance system among private healthcare practitioners providing primary care in Pune, India. Design: We mapped all private healthcare providers in three selected areas of the city, conducted a knowledge, attitude, and practice survey with regard to surveillance among 258 consenting practitioners, and assessed their willingness to participate in a routine NCD surveillance system. In total, 127 practitioners agreed and were included in a 6-month surveillance study. Data on first time diagnoses of 10 selected NCDs alongside basic demographic and socioeconomic patient information were collected onsite on a monthly basis using a paper-based register. Descriptive and regression analyses were performed. Results: In total, 1,532 incident cases were recorded that mainly included hypertension (n622, 41%) and diabetes (n460, 30%). Dropout rate was 10% (n13). The monthly reporting consistency was quite constant, with the majority (n63, 50%) submitting 110 cases in 6 months. Average number of submitted cases was highest among allopathic practitioners (17.4). A majority of the participants (n104, 91%) agreed that the surveillance design could be scaled up to cover the entire city. Conclusions: The study indicates that private primary healthcare providers (allopathic and alternate medicine practitioners) play an important role in the diagnosis and treatment of NCDs and can be involved in NCD surveillance, if certain barriers are addressed. Main barriers observed were lack of regulation of the private sector, cross-practices among different systems of medicine, limited clinic infrastructure, and knowledge gaps about disease surveillance. We suggest a voluntary augmented sentinel NCD surveillance system including public and private healthcare facilities at all levels of care.